Responses to the enlightenment : an exchange on foundations, faith and community - Sweet, William. (Value Inquiry Book Series, 2012)
Since the time of the Enlightenment in Western Europe, discussions of faith and reason have often pitted the believer against the skeptic, the theist against the atheist, and the person of one faith against the person of no professed faith. But the relation of reason to faith has been a matter of debate among believers as well. There are those who hold that religious faith can be proven or supported by rational argument. Others say that to try to give reasons and arguments does violence to religious faith, or opens it to misunderstanding and doubt, or trivializes it. Responses to the Enlightenment: An Exchange on Foundations, Faith, and Community is a dialogue between Hendrik Hart and William Sweet, two philosophers who identify themselves as Christians, and who seek to respond to the challenges of the Enlightenment and its legacy. The authors approach the relation of faith to reason, however, in very different ways: Hart from the perspective of the Calvinian tradition and postmodern philosophy, Sweet from the Catholic tradition and analytic philosophy. Among the topics discussed are the nature of religious faith and of reason, liberalism and orthodoxy in religion, the relation of religious experience and rationality, and building community in a religiously and culturally pluralistic world. This exchange presents two distinctive perspectives to some of the major challenges of the reason to religious belief, but seeks to find common ground between them.